The Influence of Live Streaming of E-Sports on Users ’Willingness ‎to Pay: Mediating Role of Immersion, Interactivity, Moderating Role of Live Streaming Platform Quality and A Chor’s Influence - Tang, Yihan; Yu, Han-Hsing (International Journal of Basic and Applied Sciences, 2025)
The rise of e-sports presents new opportunities for live streaming monetization. Understanding user willingness to pay (WP) for premium ‎content is crucial for platforms and streamers to optimize engagement and revenue, with prior research highlighting user intent, streamer ‎perception, and engagement metrics. The current investigation aims to examine the effect of live streaming on users’ WP for e-sports, with ‎an emphasis on the mediating roles of immersion (Immer) and interactivity (Inter), as well as the moderating impacts of live streaming platform quality (LSPQ) and anchor influence (ANI). A structured survey was distributed to 1,000 individuals, with 500 complete responses ‎from participants on various e-sports forums and streaming sites. The survey measured characteristics such as desire to watch e-sports ‎‎(IWLS), WP, viewer perception of the streamer (VPS), viewing metrics (VM), Immer, Inter, ANI, and LSPQ. To assess correlations ‎tween factors, the data was analyzed employing structural equation modelling (SEM) by IBM SPSS AMOS 26. The data demonstrated ‎‎(p<0.05) that Immer and Inter play an important function in facilitating the relationship between VM and WP. Furthermore, the ANI and ‎LSPQ were found to moderate these connections, thereby improving user engagement and WP. The research illustrates the value of Immer ‎as well as Inter in increasing user engagement and revenue in e-sports by streaming live, thereby improving the standard of the stream‎.